PENGARUH KOMBINASI TERAPI AKUPUNKTUR PADA TITIK SP-6 (SANYINJIAO) DAN LI-4 (HEGU) DENGAN PEMBERIAN SARI DAUN CINCAU HIJAU TERHADAP HIPERTENSI PADA LANSIA DI KELURAHAN MOJOSONGO KOTA SURAKARTA - Prabowo, Danang Aji (Universitas Veteran Bangun Nusantara, 2024)
Background: Hypertension is the third leading cause of death risk in the world after stroke and tuberculosis. Acupuncture can activate the body's defense mechanisms that affect homeostasis and promote healing in hypertension. In this study, acupuncture therapy methods at SP-6 (Sanyinjiao) and LI-4 (Hegu) points were administered by administering green grass jelly leaf extract against hypertension in the elderly. Objective: To determine the effect of a combination of acupuncture therapy at SP-6 (Sanyinjiao) and LI-4 (Hegu) points by giving green grass jelly leaf extract on hypertension in the elderly in Mojosongo subdistrict, Surakarta city. This research was conducted from September 2020 to May 2021, in the Mojosongo sub-district, Surakarta city. III, namely 14 research subjects) with the purposive sampling technique. Subject: This study used a sample of 40 research subjects divided into 3 intervention groups (group I: 13 research subjects, group II: 13 research subjects, group III: 14 research subjects) with a purposive sampling technique. Method: This study used a quasi-experimental design with a three-group pretest-posttest design. Result: The results of the Paired Sample T-Test obtained a p value <0.05, meaning that the systolic and diastolic blood pressure of the elderly decreased after Group I, Group II, and Group III were respectively given acupuncture treatment at SP-6 (Sanyinjiao) and LI- 4 (Hegu), administration of green grass jelly leaf extract, as well as acupuncture therapy at SP-6 (Sanyinjiao) and LI4 (Hegu) points by administering green grass jelly leaf extract. The results of One Way Anova obtained a p value <0.05, meaning that there was an effect of a combination of acupuncture therapy at SP-6 (Sanyinjiao) and LI-4 (Hegu) points by administering green grass jelly leaf extract to hypertension in the elderly in Mojosongo sub-district, Surakarta city. Conclusion: The combination of acupuncture therapy at SP-6 (Sanyinjiao) and LI-4 (Hegu) Points with green grass jelly leaf extract is the largest group in reducing elderly hypertension at blood pressure compared to acupuncture therapy at SP-6 Points ( Sanyinjiao) and LI-4 (Hegu) and giving green grass jelly leaf extract. Keyword : acupuncture, SP-6 (Sanyinjiao), LI 4 (Hegu), green grass jelly extract, hypertension, the elderly